Affixation in Seba Dialect of Sabu Language Used by the Sabunese in Matawaiatu Village East Sumba Regency: English - Radja, Markus; Fanggidae, Yenssy; Malelak, Deby; Isu, Rudolof (Universitas Persatuan Guru 1945 NTT, 2023)
Tulisan ini berjudul